The Impact of Oil Factor on the Car Import in Azerbaijan - Humbatova, Sugra Ingilab; Hajiyev, Natig Gadim-Ogli (International Journal of Energy Economics and Policy, 2020)
This paper analyzes the impact of oil exports and oil prices on car imports in Azerbaijan for the time span of 2010-2019 (monthly basis). There has been no study evaluating the direct effect of oil prices on import, especially, on car imports. However, similar issues have been studied in the context of the impact of oil prices on GDP or on many macroeconomic indicators of individual countries in general. The methodology used in this study is based on econometric methods which were used to analyse time series data. Stationary tests of variables (ADF, PP, and KPSS) were done. ARDL model was used as an research methodology. To investigate more specific aspects of the long run causality relationship between oil exports and oil imports, cointegration relationships are reassessed by using different econometric models such as FMOLS, DOLS and CCR. These estimates are consistent with the estimates obtained from ARDL model. Some remarkable contributions can be derived from this study toward the regulation of car imports in Azerbaijan. In general, it is concluded that in the long run, there is a positive effect of oil exports and oil prices on car imports in Azerbaijan. Keywords: oil prices, oil exports, car imports, revenues, ARDL JEL Classifications: D12, D31, F16, Q41, Q43 DOI: https://doi.org/10.32479/ijeep.9178